Assessing Multidimensional Financial Literacy Among K–10 Teachers: Knowledge, Behaviors, and Long-term Planning Attitudes - Am-una, Alexander (Journal of Interdisciplinary Perspectives, 2025)
Teachers can play a critical role in shaping learners’ financial literacy; however, there appears to be a limited research base on the financial literacy of K–10 teachers in the Philippines. This study assessed the financial literacy of K–10 teachers at the University of Baguio in three dimensions: financial knowledge, financial behaviors, and attitudes toward long-term financial planning. Using an explanatory mixed-methods design, quantitative data were gathered from 40 teachers through a stratified random sampling survey, complemented by qualitative insights from in-depth interviews with six purposively chosen participants. Informed consent and voluntary participation were ensured. Findings revealed a high mean score of 85% in financial knowledge, with strong performance in numeracy, simple interest, inflation, the time value of money, and risk–return trade-offs. However, gaps in compound interest and risk diversification indicate vulnerabilities in sustaining long-term financial security. Teachers attributed their financial knowledge largely to self-directed learning, life experiences, and family influences rather than formal education, reflecting the insufficient integration of financial literacy in the academic system. Financial behaviors were moderately positive, excelling in budgeting and making ends meet, yet revealing reliance on formal loans and limited active saving and goal setting due to fixed incomes and unexpected expenses. Attitudes toward long-term financial planning were also moderately positive, striking a balance between immediate needs and future goals, but often reactive amid income constraints and cultural pressures. Addressing these gaps requires systemic interventions, including the integration of advanced financial literacy modules into teacher education curricula and the institutionalization of school-based wellness programs in partnership with the Bangko Sentral ng Pilipinas, local banks, and accredited cooperatives. These coordinated actions represent an investment in human capital–enhancing teachers’ financial resilience and empowering them to nurture financially literate and resilient generations.